Phase Noise Cancelation Based on Polarization Modulation for Massive MIMO-OFDM Systems - Yao Nie; Chunyan Feng; Huan Wu; Fangfang Liu; Caili Guo; Maosheng Fu (International Journal of Antennas and Propagation)
In massive multiple-input multiple-output (MIMO) systems, phase noise introduced by oscillators can cause severe performance loss. It leads to common phase error and intercarrier interference in massive MIMO-OFDM uplink. To solve the issue, a novel phase noise cancelation scheme based on polarization modulation for the massive MIMO-OFDM system is proposed. We first introduce the polarization modulation (PM) exploited in massive MIMO-OFDM uplink. Then, by exploiting the zero-forcing detection, we analyze the asymptotically ICI and the distribution of the transformed noise under different XPD values. Furthermore, we demonstrate that phase noise can be asymptotically canceled and only the transformed additive white Gaussian noise exists as the number of antennas at the base station is very large. Moreover, we derive the instantaneous signal-to-noise ratio (SNR) on each subcarrier and analyze the ergodic capacity. To increase the ergodic capacity performance further, a joint modulation scheme combining the PM and 2PSK is proposed and the ergodic capacity performance of the joint modulation is discussed. The simulation results show that the proposed scheme can effectively mitigate phase noise and achieve a higher ergodic capacity.